The impact of securing the work environment on the quality of work life in the sites of Egyptian construction projects between activation and legislative and contractual responsibility - Ajrama, Fatima Abdel Mohie (Arab Journal for Sciences and Research Publishing, 2016)
The purpose of the research is to review the evolution of the legislative and contractual frameworks to take responsibility for the management of occupational safety and health and to secure the work environment. It aims to measure the extent to which engineers understand the impact of securing the work environment and the role of external bodies responsible for inspection and control and the targeted role of relevant authorities to improve the situation. The researcher concluded a survey of a random sample of 170 construction engineers with different areas and responsibilities during the first half of 2015. The research concluded that in order to achieve the safety of construction on the site, each party must assume its responsibility - each within its work - and this should be defined by the legislative frameworks and the contractual frameworks sholud pave its gaps, and this was discussed and strengthened by describing the strategy of responsibility for the management of occupational safety and health and securing the working environment in accordance with Egyptian legislation, and then presenting a set of proposals and recommendations aimed at improving the safety management situation in Egyptian construction projects.